Organizing logics, nonprofit management and change : rethinking power, persuasion and authority - Coule, Tracey M.; Bain, Carole, 1969- (New York : Routledge, 2021)
"Nonprofit organizations are conventionally positioned as generators of social and cultural forms of capital for the common good. As such they occupy a different space to other types of organization such as the corporate firm that exist primarily to generate economic capital for private owners/shareholders. Recent years, however, have seen professionalization promoted widely by funders, policy-makers and nonprofit practitioners across the globe. At the same time, there has been an increasing cross-over of employees from private and public bodies into nonprofits. But do such shifts open up space for the wholesale importation of managerialism into and commercialization of the nonprofit sphere? Are nonprofits at risk of being reconstituted as primarily economic entities, serving the interests of a leadership elite? How are such changes in an organization's trajectory brought about? What are the consequences for trustees, staff, members and the nature of managerial work? The authors engage with critical questions such as these through a unique insider account of one professional institute experiencing unprecedented changes that challenge its very reason for being. Drawing on a three-year ethnography, they narrate organizational inhabitants' struggles in their search for purpose and analyze the myriad of changes within different aspects of organizing including structure, strategizing, pay and reward, governance and leadership. The book will enable readers to reframe and rethink organizational change as a process involving power, persuasion and authority, and will be of value to researchers, students, academics and practitioners interested in managerial work and organizational change in non-profit organizations"--
OCLC-licensed vendor bibliographic record.
Keywords: Nonprofit organizations -- Management; Leadership; Organizational change; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities